Core Values of Professionalism among Fresh Medical Graduates in a Malaysian Private University - Salam, Abdus; Begum, Hamida; Zakaria, Hasbullani; Allaw, Belqees Ahmed Qaid; Han, Thuzar; Algantri, Khaleed R; Mofta, Abdulhameed Gadmor; Elmahi, Mishaal Elbasheer Babiker; Mohamed, Elamin Mhamed Elamin; Elkhalifa, Mohamed Abdelrahman Ahmed; Zainol, Jamaludin (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Core-professionalism values: altruism, accountability, excellence, respect, and integrity are unique and universally applicable to all professions. This study was aimed to investigate self-perception of core-professionalism values of medical graduates. Materials and Methods: All-50 fresh medical graduates from Widad University College session 2019 participated in this cross-sectional questionnaire survey. The questionnaire contained five core-professionalism values with 4-6 attributes under each, comprising a total of 25 attributes. The attributes were measured by a five-point Likert scale where 5=strongly agree and 1=strongly disagree. Graduates were asked to rate their selfperception on these attributes. Data were analyzed and presented as mean and percentage. Results: Response rate of the study was 92%. Male constituted 30% while females were 70%. The mean score of altruism rated as 18.58/20 (92.9%), accountability 28.01/30 (93.37%); excellence 28.57/30 (95.23%), respectfulness 23.81/25 (95.24%), and integrity 19.10/20 (95.5%). There was no significant difference of core professionalism values observed between male and female graduates. Conclusions: Fresh medical graduates scored >90% in each of the five core professionalism values which denotes the positive reputation of the organization. Core-professionalism values are unique and universally applicable to all professions and should be focused by the educators of every profession for the public good and to become responsible scientific literate citizens. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 463-472